Pengaruh Penerapan Metode Muraja’ah Pada Pembelajaran Tahfidz Al-Qur’an Terhadap Keberhasilan Menghafal Al-Qur’an (Juz 30) Siswa Kelas VI Di MI Rohmaniyah Sukawening Garut - Fauziah, Hapsah; Amelia, Risma (STAI Al-Musaddadiyah Garut, 2022)
Tahfidz Al-Qur'an learning serves as a means to enhance students' potential in understanding the Qur'an. Various methods used in Tahfidz Al-Qur'an learning play a crucial role in aligning the educational process with its intended goals. One such method is the Muraja'ah method. The Muraja'ah method in Tahfidz Al-Qur'an learning is designed to train students in reciting the Qur'an according to the principles of Tajweed and Makhrajul Huruf, while also helping to retain their memorization. This study aims to describe: The implementation of the Muraja'ah method in Tahfidz Al-Qur'an learning at MI Rohmaniyah Sukawening Garut. The success in memorizing the Qur'an (Juz 30) at MI Rohmaniyah Sukawening Garut. The influence of the Muraja'ah method on the success of memorizing the Qur'an (Juz 30) among sixth-grade students at MI Rohmaniyah Sukawening Garut. The research adopts a descriptive quantitative approach, gathering data or information related to the observed phenomena. The findings indicate that the Muraja'ah method contributes significantly to the success of Qur'an memorization, with a positive influence rate of 42.52%, which falls into the good category. Therefore, statistical tests confirm a significant relationship between the Muraja'ah method and the success in memorizing the Qur'an. Keywords: Muraja'ah Method, Tahfidz Al-Qur'an Learning, Qur'an Memorization Success